Philosophical, Social and Islamic Studies on the Criminal Acts of Theft and Corruption - Zulpahmi Lubis; Abdul Rahman (ISNU Sumatera Utara, 2024)
Theft and corruption are social problems that have existed since ancient times and continue to be serious challenges in various countries, including countries with Muslim majorities. From an Islamic perspective, these two acts are not only considered as violations of positive law, but also as major sins that damage the social and moral order of society. Islam provides clear guidance in overcoming theft and corruption, both from a legal and ethical perspective. Therefore, this study aims to examine how Islamic law regulates sanctions against theft and corruption and to find the right approach in eradicating them. This study uses a normative juridical method with a literature study approach that focuses on the analysis of sources of Islamic law, including the Qur'an, Hadith, fiqh books, and regulations in force in Muslim countries. The results of the study show that Islamic law has a firm mechanism in dealing with theft and corruption, with the main principle of upholding justice and the welfare of the people. In conclusion, Islamic law not only provides sanctions as a form of punishment, but also emphasizes preventive aspects through moral education and the formation of individuals with integrity. With a comprehensive understanding, Islam can be a solution to combating theft and corruption effectively and fairly.